Great Books of the Western World (Book 37) : Gibbon - Editor in Chief Adler, Mortimer J. (Chicago Encyclopaedia Britannica, 1993)
The author makes the point that in this abridgement he has adhered to Gibbon's style, format, planning, and footnotes, and has made only selective exclusions. The history covers the centuries from Marcus Aurelius to the capture of Constantinople, and concludes with an epilogue dealing with medieval Rome and the dawn of the Renaissance.
Include Maps
Keywords: Rome (Empire) -- Byzantine Empire